Monetary Policy and Income Inequality in the United States: The Role of Labor Unions - Josefin Kilman (Lund University, School of Economics and Management, Department of Economics, 2020)
There is a growing body of literature investigating if and how monetary policy impacts income inequality. Labor unions are generally found to mitigate income inequality and recent literature highlights that changing labor market structures, such as de-unionization, may be important for monetary policy. This paper tests whether labor unions influence the impact of monetary shocks on income inequality in the United States over the period 1970-2008, and the channels this effect runs through. This is the first paper to identify variations in unionization rates as a moderator of the impact of monetary policy on income inequality. I measure income inequality and unionization at the state level and can therefore exploit that unionization rates vary both within and across states while monetary shocks are common to all states. The main finding is that contractionary monetary shocks increase income inequality, but the impact is weaker with a higher union density. A one percentage point monetary shock increases the Gini coefficient by 5.4 % when union density is 5 %, while it increases the Gini coefficient by 1.7 % when union density is 15 %. I find evidence that both wages and employment are two channels explaining how unions mitigate the monetary policy and income inequality relationship. These findings suggest that unions make adjustments to monetary shocks more even across workers, rather than mitigating the aggregate effect of the shocks.
Keywords: D31; E24; E52; J51; 330; Monetary policy; income inequality; labor unions